Effects of soybean meal and high‐protein sunflower meal on growth performance, feed utilization, gut health and gene expression in Arctic charr (Salvelinus alpinus) at the grow‐out stage. (7th May 2018) - Smith, A.A.; Dumas, A.; Yossa, R.; Overturf, K.E.; Bureau, D.P.
Abstract: The effects of two plant ingredients (solvent‐extracted soybean meal [SBM] and high‐protein sunflower meal [HPSFM]) and three inclusion levels (0 percent, practical diet containing 25 percent fish meal; 12.5 percent; and 25 percent) of these ingredients were investigated on the growth, feed utilization, gut histology and gene expression in the distal intestine of Arctic charr Salvelinus alpinus (average initial weight, 330.1 ± 8.9 g per fish). Feeding experimental diets for 12 weeks resulted in no difference between HPSFM diets in body weight gain (BWG), thermal‐unit growth coefficient (TGC), feed efficiency (FE), feed intake (FI) or pro‐inflammatory mRNA expression (PIE) with increasing dietary inclusion and between SBM FE, FI and PIE. Differences in quadratic contrasts were observed for nitrogen deposition rate (NDR) and nitrogen retention efficiency (NRE) ( p  < .05), whereby HPSFM diets elicited the strongest positive response. SBM resulted in linear reduction in BWG, TGC and distal intestine simple fold length and width measurements ( p  < .05) with stepwise increases in dietary inclusion, whereas dietary HPSFM had no effect. Histological observations of individual villi indicated several symptoms of non‐infectious subacute gastrointestinal enteritis in tanks fed SBM, many of which were not present in tanks fed HPSFM. The dietary HPSFM seems to be more adequate to replace fishmeal in Arctic charr diet than SBM, when fed at a level of up to 25 percent at the grow‐out stage.